Effect of steam explosion modified soluble dietary fiber from Tremella fuciformis stem on the quality and digestibility of biscuits - Wang, Changrong; Lin, Mengfan; Li, Yibin; Zhuang, Weijing; Guo, Zebin (International journal of biological macromolecules, 2024)
Steam explosion (SE) technology is an effective modification method for improving resource utilization of edible fungi processing by-products. In this study, the effect of SE-modified Tremella fuciformis (T. fuciformis) stem soluble dietary fiber (SDF) on the quality and digestibility of biscuits was investigated. The results showed that the addition of SE-modified T. fuciformis stem SDF (M-SDF) changed the gluten network structure and moisture distribution in the biscuits, which improved the spread ratio of the biscuits and resulted in attractive colors. Meanwhile, as starch was embedded, the starch hydrolysis rate (from 60.9 ± 0.90 % to 43.01 ± 0.78 %) and estimated glycemic index (from 84.10 ± 4.39 to 68.45 ± 3.15) of 12 % M-SDF biscuits were reduced. Furthermore, 8 % M-SDF received the highest sensory scores. These results demonstrate the potential applicability of SE-modified edible fungi processing by-product SDF as an additive in functional foods. [Display omitted] •M-SDF hinders the formation of gluten network structure in biscuits.•Moisture distribution and texture of biscuits were affected by M-SDF addition.•Embedding of starch by M-SDF reduces its pasting and digestion.•M-SDF reduced the starch hydrolysis rate and eGI of biscuits.